Shortcomings in dealing with psychological effects of natural disasters in iran. - Ali Rabiei; Nouzar Nakhaee; Samira Sadat Pourhosseini (Tehran University of Medical Sciences, 2014)
Natural disasters result in numerous economic, social, psychological and cultural consequences. Of them, psychological consequences of disasters will affect the lives of people long after the critical conditions finish. Thus, concerning the importance of psychological support in disasters, this study has identified problems and weaknesses in dealing with the psychological effects of the disasters occurred in Iran.This qualitative study was carried out using semi-structured in-depth interviews and focus groups. Sample volume consisted of 26 experts in the field of disaster management. Content analysis was used to analyze data.Nine major problems were identified as weaknesses in handling the psychological effects of the disaster. These weaknesses include: rescuers' unfamiliarity with the basic principles of psychosocial support, shortage of relevant experts and inadequate training, paying no attention to the needs of specific groups, weaknesses in organizational communications, discontinuation of psychological support after disaster, unfamiliarity with native language and culture of the disaster area, little attention paid by media to psychological principles in broadcasting news, people's long-term dependence on governmental aid.Disaster management has various aspects; in Iran, less attention has been paid to psychological support in disasters. Increasing education at all levels, establishing responsible structures and programming seem necessary in dealing with the psychological effects of disasters.